CRIMINAL SANCTIONS FOR SPREADER OF HOAXES WITH PORNOGRAPHIC CONTENT ACCORDING TO POSITIVE LAW AND ISLAMIC CRIMINAL LAW (FIQIH JINAYAH) - Nur Aisyah; Raibullah (Journal of International Islamic Law, Human Right and Public Policy, 2023)
This research discusses the criteria for actions that are categorized as hoaxes and criminal sanctions against hoax spreaders as well as criminal sanctions for perpetrators who spread hoaxes with pornographic content according to Islamic law. perpetrators who spread hoaxes with pornographic content according to Islamic law. The research method used in this research is library research, where the data is obtained through several verses in the Al-Qur'an, hadith, and books on Islamic law, laws, mass media and articles. articles and journals. The conclusion in this research is that the criteria for hoax actions are such as creating fake news, creating trap links, creating inaccurate information, exaggerating an incident, provoking emotions so that emotions dominate more than facts, disseminating information and gossip for lies. The act of distributing pornography is regulated in Law Number 44 of 2008 concerning Pornography, if the distribution is carried out on the internet media it is regulated in Article 28 paragraph 1, 27 paragraph 1 and 27 paragraph 3 of Law Number 19 of 2016 amendment to Law Number 11 2008 concerning Information and Electronic Transactions, and criminal sanctions are regulated in Article 45 paragraph 1 with a maximum imprisonment of six years and/or a maximum fine of one billion rupiah. In Islamic criminal law, this is included in the qadzf finger. The criminal sanction for qadzf is stated in the Al-Qur'an Surah An-Nur verse 4, which is in the form of being whipped or flogged 80 times and testimony cannot be accepted forever. This punishment is absolute from Allah and cannot be increased or decreased. Apart from that, the punishment for perpetrators of distributing pornography in Islam can be ta'zir, because in Islamic law the legal certainty for the criminal act of distributing pornography has not yet been explained. This punishment will be determined by the judge in charge at a level deemed appropriate to the specified act.